(untitled) (Tempo e Argumento, 2010)
In this article I analyse two testimonies from the recent Brazilian history, especially related to the Vargas era, produced by Samuel Wainer and Carlos Lacerda. Though sometimes these journalists have tried to present their reports with the status of history, I point out that mecanisms of memory, such as selection and deformation, both attached to the present, remain in their narratives. Besides, it seems that many scholars did not consider such details and integrated their points of view without self-criticism.